A Critique on the Book Spinoza in Soviet Philosophy - seyyed Mostafa Shahraeini; Mohsen Tehrani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to introduce, criticize and evaluate Spinoza’s in Soviet Philosophy. This book is composed of seven articles of Russian thinkers about various aspects of Spinoza’s philosophy which have been written in 1920s, when the Russian Philosophers sought to reconstruct a philosophical system and there is lot of controversy among them about the nature of this system. Spinoza’s philosophical system was one of the main sources for them despite the opposite approach to this reconstruction. In 1952, The American thinker and translator, George L. Kline, with complete knowledge of the Russian and Spinoza’s Philosophy, chose and translated these articles from the different Journals of that period and published them with a detailed introduction. In this article, first, we present a general introduction of the work and its origins, then we introduce the content of each article independently and finally analyze, evaluate and criticize the various approaches.